Doughty’s The Dawn in Britain and the Modernist Eclipse of the Victorian - Tucker, Herbert (Romanticism and Victorianism on the Net, 2007)
AbstractAlthough the Modernist repudiation of things Victorian was a perfectly understandable response to postwar trauma, it is one that we still understand imperfectly at best. As the oldest and highest literary vindication to which a culture in postwar crisis could aspire, epic enjoyed an undiminished prestige that attracted some of Modernism’s best energies; but seeing Ulysses or the Cantos for what they are means affiliating them with their recent generic antecedents. A case in point, The Dawn in Britain (1906) anticipated, in its own key as a distinctly Victorian poet’s strange Edwardian epic, several problems and solutions that would engross its successors. For Doughty too meant to purify the dialect of the tribe – no matter what peculiarities of vocabulary and syntax the purge might entail – in the interest of a fearlessly direct episodic rendition of conquest and migration, always embedded within a patriotic plot of Eurasian scope and endowed with deep classical and biblical resonance. Embracing the site-perspectivism of his generation, and evincing a surprising cultural relativism to match, Doughty won among the Modernist generation who were his epic’s most impressionable first readers a following substantial enough to fund ample skepticism, in our time, about those defensive anti-Victorian slogans of theirs.